Dinamika Alat Tangkap Nelayan Pada Masyarakat Bulutui Kabupaten Minahasa Utara - Gobel, Fajrin Ramdhani; Tarmun, Alfat; Anthe, Julkivly Anjuan (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2025)
This study explores the dynamics of fishing gear usage within the fishing community of Bulutui Village, North Sulawesi, as part of a complex socio-ecological system. In this context, fishing tools such as soma (nets), menjubi (underwater spearfishing), compressors, and motorboats are not merely technical devices, but also reflect local knowledge, social solidarity, and inherited ecological adaptation strategies. Using a qualitative approach with participatory observation and in-depth interviews, this research highlights how Bulutui’s fishermen organize collective work structures in a flexible and fluid manner, grounded in trust, skills, and shared work ethics. The profit-sharing system is based on equitable contribution, governed by social norms and mutual consensus rather than formal documentation. Findings suggest that Bulutui’s fishing practices serve as a cultural resistance to exploitative economic models and provide an alternative model for sustainable fisheries management rooted in local values, social solidarity, and moral economy.